Recent experience in collaborative forest management: a review paper - Carter, J.; Gronow, J. (Center for International Forestry Research, 2005)
Collaborative forest management (CFM) is loosely defined as a working partnership between the key stakeholders in the management of a given forest—key stakeholders being local forest users and state forest departments, as well as parties such as local governments, civic groups and nongovernmental organisations, and the private sector. The paper reviews worldwide experience in CFM to date, considering the forms that it takes in different tenure situations. Overall, mechanisms of CFM are diversifying, reflecting a greater recognition of the need for partnerships in forest management. Due to entrenched power structures within both government institutions and communities, it is not easy to promote social justice and sustainable livelihoods through CFM. Nevertheless, examples exist of local people gaining a strong, legally backed voice in forest management. Whether or not CFM is financially viable depends very much on local circumstances—an important issue is the inclusion of all costs and values. CFM can clearly lead to better forest management, although examples of silvicultural innovations specifically designed to meet CFM needs are limited. Worldwide, the institutionalisation of CFM is proceeding at a different pace and to differing degrees. Whilst some of the most rapid recent CFM developments have taken place in the North, where government forest institutions are well funded and accountable, and civil society well organised, the most significant gains made to date probably lie in countries of the South and East, wherever local people have begun to enjoy real partnerships in forest management, based on recognised rights of use and access.